(untitled) - Shelton, James H (Lincolwood, Illinois, 1994)
The book takes step-by-step along the path to more effective communication: * Section 1 shows how to match your ojectives for a specific piece of communication to the needs and objectives of your audience. * Section 2 discloses the six key steps you can use to make everything you write the best: planning, organization, outlining, rough draft, revision, and final draft. * Section 3 gives a point-by point analysis of every kind of technical document. * Section 4 gives fully executed examples of technical communications written by professional technical writers, with detailed explanations of how and why they communicate so effectively
Keywords: english language,english language,technical writing; rhetoric,handbooks, manuals, etc,technical english,handbooks, manuals, etc,handbooks, manuals, etc